1999
DOI: 10.1038/sj.bjc.6690576
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum-soluble CD95 (Fas/APO-1) on prognosis in renal cell cancer patients

Abstract: Summary Serum-soluble CD95 (sCD95) levels for 72 renal cell cancer patients were significantly higher than those of 17 healthy donors. Twenty-one of 72 patients had elevated (defined as more than mean of healthy donors + 2 s.d.) sCD95. The disease-specific survival rate was significantly lower in the elevated sCD95 group. Serum sCD95 level was shown to be an independent prognostic factor by univariate and multivariate analysis, indicating a possible significant role in determining treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Many previous studies have reported that serum sFas is elevated in patients with malignant disease [39,40]. Several studies have been performed showing an increased sFas serum concentration associated with a poor prognosis in patients suffering malignant disease [41,42]. Previous studies have also reported that the sFas levels were increased in the plasma from patients with inflammatory situations such as SIRS [23,32,42,43] and coronary bypass surgery [33].…”
Section: Discussionmentioning
confidence: 91%
“…Many previous studies have reported that serum sFas is elevated in patients with malignant disease [39,40]. Several studies have been performed showing an increased sFas serum concentration associated with a poor prognosis in patients suffering malignant disease [41,42]. Previous studies have also reported that the sFas levels were increased in the plasma from patients with inflammatory situations such as SIRS [23,32,42,43] and coronary bypass surgery [33].…”
Section: Discussionmentioning
confidence: 91%
“…Renal cell cancer has been reported to harbour mutations in exons 7 and 9 of the Fas gene (Takayama et al, 2002). Indeed, we have previously demonstrated that RCC patients have elevated levels of soluble Fas, which was an independent negative prognostic factor (Kimura et al, 1999). In addition to inducing apoptosis, Fas can also promote cell growth or differentiation (Mapara et al, 1993;Owen-Schaub et al, 1994;Budd, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…We previously investigated several apoptotic factors, together with their signalling mechanism and reported the prognostic value of serum soluble Fas in RCC patients (Kimura et al, 1999). Furthermore, the frequent expression of Bcl-2 and the absence of p53 gene alterations were found in these RCC specimens (Tomita et al, 1996b).…”
mentioning
confidence: 99%
“…Furthermore, a correlation of the serum sFas level with the prognosis of patients was observed in several studies. [22][23][24][25] However, little is known about the level of sFas in malignant pleural effusion and the sFas expression of lung cancer.…”
mentioning
confidence: 99%